In vitro seed germination, callus induction and naphthodianthrones production in Hypricumm triquetrifolium Turra - Azeez, Hoshyar A.; Ibrahim, Kadhim M. (Sulaimani Journal for Pure and Applied Sciences, 2017)
The present study was designed to investigate seed germination and callus induction in vitro and to produce (naphthodianthrones) hypericin and psudohypericin in Hypericum triquetrifolium Turra tissue cultures. Seeds were germinated aseptically on MS medium and water agar medium. Seeds germinated on water agar were better than those germinated on ½ MS medium. Germination percentage increased after treatment with GA3 at 100 mg L-1. Leaf, stem and root explants were excised from in vitro grown seedlings. Callus was initiated on the leaf discs which were previously cultured on MS medium supplemented with Thidiazuron (TDZ) at different concentrations included 1.0, 1.25, 1.5, 2.0, or 2.5 mg L-1 and indole-3-acetic acid (IAA) at 0.5 mgL-1. It was observed that the combination of TDZ at 2 mg L-1 with 0.5 mg L-1 IAA supplemented to MS medium, yielded the highest fresh and dry weights of callus initiated on leaf explants. The same combined mixture was used for callus maintenance, The same components described for callus maintenance medium devoid agar, was used for initiating cell suspension cultures. To define the type and quantity of the secondary metabolites, HPLC was depended. Hypericin and pseudo-hypericin were not detected in calli, and cell suspension cultures initiated on leaf explants, while they were detected in calli and cell suspension cultures initiated on stem and root explants.
Keywords: Hypericum triquetrifolium; Callus; Hypericin and Psudohypericin; HPLC